2013
DOI: 10.1590/s1517-83822014005000012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alcohols on filamentation, growth, viability and biofilm development in Candida albicans

Abstract: In this study we report the potential of alcohols as morphogenetic regulators in Candida albicans. All the alcohols tested influenced various modes of growth like planktonic as well as biofilm forms. Viability was affected at high concentrations. Among the alcohols, the response of C. albicans to amyl alcohol (pentanol) was noteworthy. Amyl alcohol at a concentration 0.5% which was not inhibitory to growth and viability specifically inhibited morphogenetic switching from yeast to hyphal forms. It also inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…The importance of upregulating fermentation in biofilms is unknown, but we recently showed that the inside of a C. albicans biofilm is a hypoxic microenvironment (Fox et al ., ), favorable for fermentation. We suggest that alcohols produced during fermentation may be used for energy or could be involved in cell signaling with neighboring yeast or other microbes; some alcohols have been shown to alter biofilm formation (Mukherjee et al ., ; Martins et al ., ; Rane et al ., ; Chauhan et al ., ). Overall, our analysis reveals that the regulation of metabolism genes in biofilms does not simply parallel that in stationary cultures.…”
Section: Resultsmentioning
confidence: 97%
“…The importance of upregulating fermentation in biofilms is unknown, but we recently showed that the inside of a C. albicans biofilm is a hypoxic microenvironment (Fox et al ., ), favorable for fermentation. We suggest that alcohols produced during fermentation may be used for energy or could be involved in cell signaling with neighboring yeast or other microbes; some alcohols have been shown to alter biofilm formation (Mukherjee et al ., ; Martins et al ., ; Rane et al ., ; Chauhan et al ., ). Overall, our analysis reveals that the regulation of metabolism genes in biofilms does not simply parallel that in stationary cultures.…”
Section: Resultsmentioning
confidence: 97%
“…), but other alcohol‐based autoregulating substances produced in these conditions can promote the dissemination of yeast cells from the biofilm, thereby inhibiting biofilm development (Chauhan et al . ).…”
Section: Quorum Sensing Moleculesmentioning
confidence: 97%
“…Farnesol secreted from C. albicans yeast cells has been also shown to stop germ tube formation in the later stage of biofilm development, as well as under other hyphal-inducing conditions (Hornby et al 2001;Alem et al 2006), and therefore, acts as a repressor of the switch from yeast to hyphal growth (Ramage et al 2002), but it is unable to block the elongation of pre-existing hyphae (Mosel et al 2005;Navarathna et al 2005). Under anaerobic conditions, farnesol is not produced (Sato et al 2004), but other alcohol-based autoregulating substances produced in these conditions can promote the dissemination of yeast cells from the biofilm, thereby inhibiting biofilm development (Chauhan et al 2013).…”
Section: Quorum Sensing Moleculesmentioning
confidence: 99%
“…ALD6 is involved in alcohol production during fermentation and is up regulated in the hypoxic microenvironment of mature biofilms (Fox et al, ). Alcohol production may be involved in providing energy and/or may serve as signalling molecules for cell–cell communication (Chauhan, Shinde, & Karuppayil, ; Mukherjee et al, ; Rane, Bernardo, Walraven, & Lee, ). Furthermore, the mitochondria and membrane/transport networks are connected via glutathione‐transferase putative gene ( GTT12 ) and the oligopeptide transporter ( OPT1 ).…”
Section: Resultsmentioning
confidence: 99%